Telaah Yuridis terhadap Putusan Mahkamah Konstitusi Nomor: 92/PUU-XXII/2024 dalam Perkara Pengujian Undang-Undang Desa - Muh. Fadil; Ahmad Rustan; Multi Sri Asnani (CV Rewang Rencang, 2025)
The simultaneous election of Village Heads (Pilkades) in South Konawe Regency on September 24, 2023 is crucial after the issuance of Law Number 3 of 2024. Although the Constitutional Court in Decision Number 92/PUU-XXII/2024 stated that the Regional Elections were in accordance with Law Number 6 of 2014 concerning Villages, the facts are contrary to Article 32 paragraph 1 of the Village Law regarding the notification of the end of the term of office of the village head. This research aims to analyze the Constitutional Court's considerations in case 92/PUU-XXII/2024 from the perspective of justice and the principle of the rule of law. This research employs a normative legal method, utilizing both a statutory approach and a case approach, with a focus on examining Article 118, letter e of Law Number 3 of 2024. The Constitutional Court judge's consideration that the Regional Elections in South Konawe were by the Village Law factually contradicted Article 32 paragraph 1 of Law Number 6 of 2014. A total of 94 village heads still have 7 months remaining in office and 2 other village heads 14 months when the election is held, even though the notice of term of office should have been made 6 months in advance. This makes the Constitutional Court's consideration juridically flawed and contrary to the principle of the rule of law, so that the applicant's application should be rejected.